Development of niobium-promoted cobalt catalysts on carbon nanotubes for Fischer-Tropsch synthesis - Ali, S. (Elsevier, 2011)
Cobalt-based catalysts were prepared using wet impregnation method on carbon nanotubes (CNTs) support and promoted with niobium. Samples were characterized by nitrogen adsorption, TEM, XRD, TPR, TPO, and TPD. Addition of niobium increased the cobalt dispersion but decreased the catalyst’s reducibility. Fischer-Tropsch synthesis (FTS) was carried out in a fixed-bed microreactor at 543 K, 1 atm and H2/CO=2 for 5 h. Addition of niobium enhanced the C5+ hydrocarbons selectivity by 39 % and reduced methane selectivity by 59%. These effects were more pronounced for the 0.04%Nb/Co/CNTs catalyst, compared to those observed for other niobium compositions.